Freight wagons in Turkey: A comparative study - Kilinc, Onur (Univerzita Pardubice, 2014)
This research includes an overview of most common freight wagons and a detailed investigation of different carbodies that are used in Turkey by making a brief comparison of railway technology between Turkey and other countries. The investigation includes the current development of Turkish railways compared to road transportation during more than a decade. Concurrently, the paper examines transport needs, which is planned to be highly improved in the near future by means of railway transportation, strategically, due to 75 billion dollars of potential between Europe and Asia. Throughout this research, not only structural information like wagon types, structure of their bodies, floor types, special equipment presence and suitable cargo types but also a contemporary comparison, in the light of the data provided by Organisation for Economic Co-operation and Development (OECD) and Turkish State Statistics (TUIK), of Turkish transportation capabilities with its past and other countries are told.